Parental Education and Child?s Education : A Natural Experiment - Arnaud Chevalier (Institute for the Study of Labor (IZA), 2004)
Is the intergenerational educational link due to nature or nurture? In order to answer this dilemma, this paper identifies the effect of parental education on their offspring?s schooling attainment using a discontinuity in the parental educational attainment. The discontinuity stems from changes in the minimum school leaving age legislation which took place in the Seventies in Britain. This strategy identifies the effect of parental schooling only for parents with a lower taste for education and may not reflect the general social returns of parental education. However, since policies are more likely to target children at risk of not maximising their educational potential, the estimates are of interest. Contrary to recent evidence, we find a positive effect of both parents education on their children?s schooling achievements when focusing on natural parents only. Step parents have no or a negative impact on children?s education. In most cases, the endogeneity of parental education is rejected. These estimates suggest substantial social returns to education for same-sex parent. The estimates are robust to the introduction of additional controls for income, labour force participation, fertility and neighbourhood quality, indicating that the effect of parental education is direct.
Keywords: I20; J62; 330; educational choice; intergenerational effect; Bildungsverhalten; Eltern; Bildungsniveau; Kinder; Generationenbeziehungen; Schätzung; Grossbritannien